Rancang Bangun Troli Multifungsi Kapasitas 100 Kg - Rahmatullah, Rahmatullah; M, Muharnif; Nasution, Arya Rudi; Barus, Syahputra; Octariza, Gintara (Rekayasa Material, Manufaktur dan Energi, 2026)
Technology to facilitate human activities in lifting and transporting work continues to develop. Trolleys are tools that can help move goods. The design of the trolley is planned to be able to transport simply but strong and stable. This trolley is made using plate materials, iron pipes and others in its manufacture. The materials are selected to ensure durability against heavy loads. The trolley lifting system is an electrical system that includes a battery, an electric motor, and a switch to control the trolley automatically. The trolley is made using 19 mm iron pipes, wheels, 3 mm iron plates, a transport body frame made of 58 mm iron pipes and also the drive or carrier is a 5 mm steel sling with 2 pcs electric motor batteries with a power of 12 volts each. The trolley made can carry an effective load of around 100 kg, but its performance will decrease as the load increases. Future suggestions are the use of lighter but stronger materials such as aluminum or composites, the use of larger capacity and efficient electric motors, and testing with a wider variety of loads to understand the limits and maximum performance of the trolley. Training in proper use and maintenance of the trolley is recommended to ensure optimal condition and maximum service life.